Pengaruh ZIS dan Korupsi Terhadap Ketimpangan Pendapatan Tahun 2010-2019 di Indonesia - Reska Prihatini (2021)
This study aims to explain and find out how much influence ZIS (Zakat, Infak, and Alms) and corruption have on income inequality in Indonesia. This study uses a saturated sample, with data sourced from data from Badan Amil Zakat Nasional (BAZNAS), Transparency International, and Badan Pusat Statistik (BPS). This study uses quantitative data types, time series data, namely the time series from 2010 to 2019, with multiple linear regression IBM SPSS Statistics 26 as data processing. The findings of this study indicate that ZIS has a significant negative effect on income inequality. While the corruption variable has a significant positive effect, this is because Indonesia has a history of corruption. So in situations where institutions are not well developed, corruption can help in building the economy and be an effective substitute for bad institutions, and missing laws. Furthermore, the results of the study show that ZIS and corruption have a joint effect on income inequality.